Apuleius’s De Deo Socratis: A Translation and Commentary - Jaskelevičius, Alius (Literatūra, 2018)
[text in Lithuanian; abstract in English] This publication consists of the first published Lithuanian translation of Apuleius’s De deo Socratis, accompanied with a comprehensive commentary. Apuleius’s De deo Socratis examines the subject of daemons, which was very popular in the thought of Middle Platonism. In his treatise, Apuleius not only presents a general theory of daemons but gives authorial insights into the theme as well. Apuleius emphasizes the cosmological and theological aspects of the theory of daemons and their importance for practical behavior.